The influence of thermal conditions on potato yield in the administrative regions of the Republic of Belarus - Davydenko, Olga V.; Lopukh, Piotr S. (Journal of the Belarusian State University. Geography and Geology, 2019)
The analysis of the dynamics of thermal conditions during 1961–1988 and 1989–2015, as well as the adjacent decade of the study period. Changes were estimated for the average temperatures of individual months of the year, high average and maximum daily temperatures, as well as for the duration of the active vegetation period and the sums of active temperatures. The established increase in average annual temperatures was 0.4 °С per decade. At the same time, in the first half of potato vegetation (May – June) the thermal trends are ambiguous, while in the second half (July – August) the increase of average air temperatures prevails. The increase in temperatures in the summer months is accompanied by an increase in the prevalence of negative thermal effects on potato yields, which is confirmed by negative correlation coefficients of potato yield deviations from trend lines and indicators such as the air temperature in July and the number of hot days (with an average temperature above 20 °С and a maximum temperature above 30 °С). Statistical reliability of correlation between potato yield deviations from trend lines and July temperatures is confirmed only in 1989 –2015 and covers 60 administrative districts. In these and most of the remaining areas, the correlation coefficients are negative. It is established that the proposed and justified critical value of the number of days with a maximum temperature above 30 °С (10 and more) determines more than a third of the negative deviations of potato yield in most of the country, and the probability of its negative impact in the modern period is 70 %. The decrease in average yield is 12.7 c/ha (8 %). It was found that the most unfavorable hot period occurs during the tuber formation and growth of potato tubers, in connection with which possible measures of adaptation of potatoes to temperature increase are proposed: the use of heat-resistant potato varieties, the shift of potato planting dates to earlier dates, irrigation (in the case of a combination of high temperatures with insufficient moisture).
Keywords: air temperature; dangerous weather phenomena; heat; potato; productivity fluctuations